Membendung Gelombang Judi Online di Kalangan Santri: Strategi Preventif Berbasis Pendidikan Karakter - Dwi Novitasari; Zujajatul 'Ilmi; Riyan Sisiawan Putra; Ninnasi Muttaqiin; Mukhtar Adinugroho (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2025)
Stemming the Wave of Online Gambling among Santri: An Education-Based Preventive Strategy The increasing involvement of teenagers in online gambling activities raises concerns about the quality of the nation's next generation. This is triggered by easy access to the internet, low digital understanding, and the influence of a less supportive social environment. This community service activity aims to build awareness and understanding of middle school students regarding the risks of online gambling through a series of educational activities, socialization, and psychosocial assistance. The approach used includes interactive delivery of educational materials, life skills training, formation of peer support communities, and counseling services. Program implementation is carried out through synergy between schools, experts, students, and volunteers. This program is expected to increase digital understanding, the ability of adolescents to make wise decisions, and create a safe and supportive digital environment. This activity is a form of applying the results of previous research related to risk factors for online gambling, which are then realized in the form of educational programs in schools. Evaluation was conducted to assess the success of the activity and design sustainability efforts through digital campaigns and school community involvement. Through a holistic and collaborative approach, this program is expected to encourage the formation of a strong young generation free from online gambling practices.